TEACHERS’ PEDAGOGICAL COMPETENCE IN TEACHING ENGLISH AT JUNIOR HIGH SCHOOL - Nurliyanti Nurliyanti; Nadrun Nadrun; Maf'ulah Maf'ulah (e-Journal of ELTS (English Language Teaching Society), 2022)
This research focuses on pedagogical competence of English teachers’. This research aims to find out pedagogical competence of English teachers in teaching English at SMP Negeri 13 Palu. Data collection techniques used were questionnaire, interview and observation. The observation was used to find out the students perception on the teacher's pedagogical competence in teaching English. The interview was used to determine the pedagogic competence of teachers in teaching English. The observation was also used to see the process of teaching English in the classroom. The result of questionnaire showed that students’ perceive on English teachers’ when teaching English were very good pedagogical competence in mastering the characteristics of students, ability to develop curriculum/syllabus, developing students potential and evaluation of learning outcomes. The results of interviews with four English teachers showed that there were some difficulties in learning they are in the use of technology and developing the potential of students. The results of the observations show that the pedagogic competence of four English teachers in teaching English is in the good. In general, the pedagogical competence of the English teacher at SMP Negeri 13 Palu is generally in good criteria.